NEW OUTLOOK FOR SHARIA COOPERATIVE PERFORMANCE MEASUREMENT IN INDONESIA - Rita Mutiarni; Ubud Salim; Eko Ganis Sukoharsono; Mintarti Rahayu (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
Cooperatives are one of the supporters of the economy in Indonesia, but unfortunately, so far the development of cooperatives in Indonesia, especially sharia cooperatives, is still not good. This is based on a report issued by the office of cooperatives and micro, small and medium enterprises in Indonesia which states that the development of cooperatives in Indonesia is still slow. This can be seen from the financial statements of cooperatives which are used as indicators by the government to measure the performance of cooperatives, especially sharia cooperatives. This paper provides a new perspective to measure the performance of cooperatives, not only from financial indicators but also from non-financial indicators. This is because cooperatives are not purely business organizations to seek profit from their business activities, but also have a social mission for the stakeholders in the cooperative. Keywords: new outlook, measurement, cooperative, sharia, non-financial indicator.